2021
DOI: 10.3389/fpls.2021.660012
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Identity, Diversity, and Population Structure of CIP's Sweetpotato (I. batatas) Germplasm Collection

Abstract: The in trust sweetpotato collection housed by the International Center of Potato (CIP) is one of the largest assemblages of plant material representing the genetic resources of this important staple crop. The collection currently contains almost 6,000 accessions of Ipomoea batatas (cultivated sweetpotato) and over 1,000 accessions of sweetpotato crop wild relatives (CWRs). In this study, the entire cultivated collection (5,979 accessions) was genotyped with a panel of 20 simple sequence repeat (SSR) markers to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 32 publications
0
17
0
1
Order By: Relevance
“…Not only were regional pairwise genetic differentiation and distance values for South America higher than average (F ST ≥ 0.71, genetic distance ≥ 0.48), Bayesian clustering exhibited minor admixture with other geographic regions. Upon population structure analysis of the CIP collection, Anglin et al suggested that accessions from Peru had been genetically isolated over time (Anglin et al, 2021). Of the 85 accessions from South America clustered in DAPC cluster 2 (Figure 3A and Table 3), 84 were from Peru, further confirming this idea.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Not only were regional pairwise genetic differentiation and distance values for South America higher than average (F ST ≥ 0.71, genetic distance ≥ 0.48), Bayesian clustering exhibited minor admixture with other geographic regions. Upon population structure analysis of the CIP collection, Anglin et al suggested that accessions from Peru had been genetically isolated over time (Anglin et al, 2021). Of the 85 accessions from South America clustered in DAPC cluster 2 (Figure 3A and Table 3), 84 were from Peru, further confirming this idea.…”
Section: Discussionmentioning
confidence: 76%
“…Germplasm from 2 USDA collections (n=417) found that accessions were clustered into 4 genetic groups ( Wadl et al., 2018 ), whereas an analysis of accessions primarily from China (n=197) found that 3 genetic groups best describe the material in that collection ( Su et al., 2017 ). More recently, the International Center of Potato (CIP) genotyped 45% of the collection (n=5,979) using 20 simple sequence repeat markers and concluded 4 genetic clusters best describe the collection ( Anglin et al., 2021 ). While it is difficult to discern true population structure and clusters, we found that historical and experimental evidence from this study suggests that K=6 may better encapsulate sweetpotato population structure of the PGRCU collection.…”
Section: Discussionmentioning
confidence: 99%
“…Beginning in the 1990s, molecular markers based on allelic polymorphisms were developed, and they have been widely utilized to estimate genetic diversity in sweetpotato. Early studies of sweetpotato used a variety of markers, including restriction fragment length polymorphisms (RFLPs), random amplified polymorphic DNA (RAPD) ( Jarret and Austin, 1994 ; Gichuki et al., 2003 ), amplified fragment length polymorphisms (AFLPs) ( Zhang et al., 2000 , 2004 ), inter-simple sequence repeats (ISSRs) ( Li et al., 2008 ; Moulin et al., 2012 ), ESTs ( Marian et al., 2018 ), and simple sequence repeats (SSRs) ( Veasey et al., 2008 ; Som et al., 2014 ; Yang et al., 2015 ; Zawedde et al., 2015 ; Feng et al., 2018 ; Lee et al., 2019 ; Palumbo et al., 2019 ; Anglin et al., 2021 ). These markers have been used to characterize and define the accessions in sweetpotato germplasm collections and to examine population structure and gene pools of sweetpotato originating from Latin America, South America, Central America, Oceania, Asia, and Africa ( Zhang et al., 2000 ; Gichuki et al., 2003 ; Li et al., 2008 ; Som et al., 2014 ).…”
Section: Polyploid Genetics Of Sweetpotatomentioning
confidence: 99%
“…Although the in vitro storage period can be extended to 2-3 years between subcultures or propagation cycles, the plant material needs to be renewed periodically and any handling of the genebank material exposes the collection to the risk of human error (mix up of accessions), fungi or bacteria contamination, or somaclonal variation sometimes produced from tissue culture. As the renewal process occurs repeatedly, the probability of changes, due to human error or biology of the conserved material, can add up over time ( Anglin et al., 2021 ). Many of the above-mentioned disadvantages can be lessened, mitigated, or eliminated using cryopreservation for clonal crop maintenance.…”
Section: Introductionmentioning
confidence: 99%